The Problem of Being in “Disputationes Metaphysicae” of Suarez and “Logica” of M. Smiglecki - Jonkus, Dalius (Problemos, 1996)
M. Smiglecki (1586-1618) is a famous representative of the late Scholasticism in Lithuania. He was a teacher of philosophy and theology at Vilnius University in 1586-1599. His two-volume work “Logica” was published in Ingolstadt and republished three times (1634, 1638, and 1658) in Oxford. The problem of intelligible being is analysed in the last disputation by Suarez, and in the first by Smiglecki. He considers this as being the metaphysical presupposition of logic. The Smiglecki conception of intelligible being is identical with that of Suarez's. Both thinkers oppose intelligible being to real being; they both ontologize the logical principle of noncontradiction, transforming it into the ground of real possible being.